PENGARUH IMPLEMENTASI KEBIJAKAN TERHADAP EFEKTIVITAS PEMBANGUNAN INFRASTRUKTUR DI DESA PANYADAP KECAMATAN SOLOKANJERUK KABUPATEN BANDUNG - Aisyah, Pratiwi; Indah, Diani (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
The problem in this research is the ineffectiveness of infrastructure development in Panyadap Village, Solokanjeruk District, Bandung Regency. Based on these problems, the researcher formulated the problem as follows: How Big is the Influence of the Implementation of Panyadap Village Government Policies on the Effectiveness of Infrastructure Development in Panyadap Village, Solokanjeruk District, Bandung Regency. In analyzing the problems studied, the authors propose the theory of policy implementation from George C Edwards III (in Subarsono 2011: 90- 92) with the dimensions of Communication, Resources, Disposition/Attitude and Bureaucratic Structure. While the theory of effectiveness from Duncan in Steers (2008:53) with dimensions namely Goal Achievement, Integration, and Adaptation. Based on this framework, the hypothesis formulated is: